Examining failures in rubber-cord couplings within ER2 series electric trains - Gavrilovs, Pavels; Gorbacovs, Dmitrijs; Eiduks, Janis; Strautmanis, Guntis; Arshad, Ali (Transport, 2024)
The article provides statistics on failures of rubber-cord couplings of electric trains of the ER2 and ER2T series and of the diesel trains over the past 7 years. According to statistics, over the past 7 years, 107 rubber-cord couplings have failed. Of these, the largest number of cases of failure of rubber-cord couplings occurred on rolling stock of the ER2 series. Examining failed rubber-cord couplings, it was revealed that the cause of its failure was a rupture of the side surface. Replacing a rubber-cord coupling is a labour-intensive and costly process. Accordingly, the question arises: what causes the problem and what measures should be proposed to reduce the failures. For these purposes, the work presents a number of experiments in order to identify possible causes of failure of the rubber-cord coupling. The article presents studies of the heating temperature of rubber-cord couplings in operation on motor cars, as well as a number of studies of failed rubber-cord couplings removed from motor cars. During the research, such parameters as the date of the last repair and the date of failure of the rubber-cord coupling were taken into account. The number of days the motor car was in general operation was taken into account until the failure of the rubber-cord coupling, as well as the mileage of the motor car after the repair. Measurements were carried out of the geometric parameters of the rubber-cord coupling: outer and inner diameter, thickness of the side of the rubber-cord coupling. The torque of the rubber-cord coupling acting at speeds from 5 to 40 km/h, the forces acting in operation on the rubber-cord coupling were calculated, and torsional and shear stresses were also studied and determined. Research was carried out to determine the hardness of the rubber-cord coupling in the temperature range from –20 °C to 0 °C and from 0 °C to +22 °C, as well as from +22 °C to +60 °C. These parameters were taken since a rubber-cord coupling operates under the mentioned conditions. In conclusion, possible reasons for the failure of rubber-cord couplings are given, and recommendations for reduction of their frequency are proposed.